CROSS-BORDER INSURANCE MARKETING AND THE CORPORATE IMPLICATIONS - Epetimehin, F. M. (European Scientific Journal, ESJ, 2013)
The present investigation has been undertaken in order to study the decision-making involved in the process of cross border marketing planning, the competences that can be developed to respond creatively to the changing global environment in the light of cross border marketing challenges. A simple study was carried out through questionnaire. 156 senior executives of insurance companies with cross border insurance companies were carefully sampled randomly. Also the grounded theory was used to summarize the answers to some of the questions posed to some of the Chief Executives and Executive directors of insurance companies involved in cross-border marketing. Qualitative data collected was analyzed using content analysis Quality will be the ultimate yardstick in cross border competition, and quality will be determined by professional competence. Thus, developing global leadership in insurance entails paradigm shifts. These often require the development of new organizational mindset, knowledge and competences, and will require the organizations to engage in long term planning and sustainable implementation. On a global level the only insurers able to compete will be those that have the leadership and staff capacities to respond to ever more complicated client needs.